2008
DOI: 10.1021/jf8007053
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Antioxidant Activity in Vitro and in Vivo of TwoFucus vesiculosusExtracts

Abstract: The consumption of seaweeds has increased in recent years. However, their adverse and beneficial effects have scarcely been studied. Two extracts from the brown seaweed Fucus vesiculosus containing 28.8% polyphenols or 18% polyphenols plus 0.0012% fucoxanthin have been obtained and studied to determine their toxicity in mice and rats and also their antioxidant activity. Both extracts were shown to lack any relevant toxic effects in an acute toxicity test following a 4 week daily treatment in rats. The extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 35 publications
5
75
2
Order By: Relevance
“…Reactive oxygen species are known to cause cellular damage, which is implicated in the pathogenesis of disorders such as cardiovascular disease, cancer, metabolic syndrome, and type II diabetes. A study by Zaragozá et al (2008) on the antioxidant effect of an extract of Fucus vesiculosus containing 0.0012 % fucoxanthin, found that antioxidant activity increased in ex vivo assays of erythrocytes and plasma, after 4 weeks of daily oral administration in rats. Significant antioxidant activity was also observed in non-cellular systems and in activated RAW 264.7 mouse leukaemic monocyte macrophage cell lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive oxygen species are known to cause cellular damage, which is implicated in the pathogenesis of disorders such as cardiovascular disease, cancer, metabolic syndrome, and type II diabetes. A study by Zaragozá et al (2008) on the antioxidant effect of an extract of Fucus vesiculosus containing 0.0012 % fucoxanthin, found that antioxidant activity increased in ex vivo assays of erythrocytes and plasma, after 4 weeks of daily oral administration in rats. Significant antioxidant activity was also observed in non-cellular systems and in activated RAW 264.7 mouse leukaemic monocyte macrophage cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment group showed a significant increase in resting energy expenditure and mean weight loss of 4.9 kg after 16 weeks. No toxicity of fucoxanthin extracts has been reported to date, making it an excellent candidate for nutraceutical applications (Maeda et al 2007;Zaragozá et al 2008) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of several studies on the biological activities of fucans, detailed studies on the toxicology of fucans from different sources are limited. Few studies have shown that some algal fucans are not toxic compounds (Li et al, 2005;Gideon & Rengasamy, 2008;Zaragozá et al, 2008;Chung et al, 2010). However, each new fucan purified from a marine alga is a new compound with unique structures and, consequently, with potential pharmacological and toxicological properties.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the consumption of seaweeds has increased many folds because of their beneficial effects and no adversity. The in vitro and in vivo antioxidant activities of edible F. vesiculosus extract were studied Zaragoza et al (2008). The extracts showed no toxicity effects in the acute toxicity studies in mice and rats.…”
Section: Seaweed Antioxidantsmentioning
confidence: 99%